2020
DOI: 10.22271/ortho.2020.v6.i1f.1880
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of PFN A2 vs bipolar hemiarthroplasty in unstable senile intertrochanteric fractures

Abstract: Introduction: Successful outcome in the treatment of intertrochanteric fracture in elderly lies in early mobilization of the patient so as to avoid the morbidity, complications and poor recovery. With the associated medical comorbidities and osteoporosis, presents a great challenge in selecting the surgical procedures in these patients. Even though the primary choice of surgery revolves around Osteosynthesis in these type of fractures, there is a conspiracy in the choice of implants for the fractures. Many sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Another study done by Vuppala et al [6] reported similar results in which scores were calculated at the fourth and sixth-month follow-up, and significant results were found with scores being 80.55 and 83.25 in the hemiarthroplasty group and 68.89 and 72.47 in the osteosynthesis group, respectively. Venkatraman et al [14] reported similar results in their study in favor of the hemiarthroplasty group.…”
Section: Studymentioning
confidence: 52%
See 2 more Smart Citations
“…Another study done by Vuppala et al [6] reported similar results in which scores were calculated at the fourth and sixth-month follow-up, and significant results were found with scores being 80.55 and 83.25 in the hemiarthroplasty group and 68.89 and 72.47 in the osteosynthesis group, respectively. Venkatraman et al [14] reported similar results in their study in favor of the hemiarthroplasty group.…”
Section: Studymentioning
confidence: 52%
“…There was one episode of dislocation in this study in the hemiarthroplasty group (3.33%). Other studies in the literature reported similar results, with Prasad et al [2] reporting an incidence of 3.7% in the hemiarthroplasty group and Venkatraman et al [14] reporting a single incidence of dislocation (5%) in the hemiarthroplasty group. While other authors such as Gokay et al [5], Nadir et al [7], and Patil [13] did not encounter an incidence of dislocation in their studies.…”
Section: Study Limitationsmentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast, BHA requires no time for fracture union, has lower implant failure, and allows the patient to compress with full load postoperatively. 4,5 Previous studies have reported that in-hospital mortality rates following hip fracture surgery vary between 2.7% and 15%, while 1-year mortality rates vary between 11.5% and 58.3%. 6 Many factors affecting mortality and morbidity in patients operated for hip fracture exist, including age, comorbidities, operation duration, and surgical technique.…”
Section: Introductionmentioning
confidence: 99%